Relatório de viagem ao exterior [Kingston, Jamaica] - SOUZA, Kaiser Gonçalves de (2006)
Workshop Mining of Cobalt-rich Ferromanganese Crust and Pollimetalic Sulphides: Technological and Economic Considerations